Efeitos da covid-19 na função visual de contraste para grades senoidais em adultos - Silva, Gabriella Medeiros (2022)
There are many gaps as to the extent of damage caused by COVID-19. An example is the absence of publications relating it to the Contrast Sensitivity Function (CSF). In this sense, the objective of the present study was to evaluate the CSF for low spatial frequencies; averages and highs in people with and without a history of COVID-19. Thirty volunteers, aged between 18 and 49 years, divided into two groups, based on the presence or absence of the diagnosis of COVID-19, participated: Study Group (GE; M= 28.00; SD= 8.92 years) and Control Group (CG; M= 26.27; SD= 4.89 years). The following instruments were used: Sociodemographic and clinical data questionnaire, Mini Mental State Examination (MMSE), Beck Anxiety and Depression Inventories (BAI and BDI II) and the COVID-19 Subjective Scale of Sensory and Perceptual Anomalies (SSSPA- COVID-19). CSF was measured using the Metropsis software (version 11), using vertical sinusoidal grids for spatial frequencies between 0.2 and 19.8 cycles per degree of visual angle (cpd) as stimuli. The results indicated that there is an effect of COVID-19 for CSF on spatial frequencies 6.1 (U = 36.000; p = 0.003; r = - 0.55), 13.2 (U = 29.000; p = 0.001; r = - 0.61), 15.9 (U = 17.000; p = 0.001; r = - 0.70) e 19.8 cpd (U = 13.000; p = 0.001; r = - 0.73).]. This demonstrates a reduction in contrast sensitivity for high spatial frequencies, signaling that COVID-19 seems to affect mainly the left hemisphere, associated with analytical information processing and that it appears to be more specialized in processing high spatial frequencies. Thus, it is assumed that the disease can impair the processing of fine details, such as edges and corners at high contrast levels. However, the data are still preliminary and further studies are needed to better assess the effects of COVID-19 on visual functions.